Problems in the Construction of a Deed of Separation of Joint Property After Divorce Without a Court Decision - Dewi Tjandraningsih (The International Journal of Law Review and State Administration, 2026)
The distribution of joint property (marital assets) after a divorce is ideally conducted based on a court decision to ensure legal certainty. However, in practice, many parties choose to divide their assets through a Notarial Deed without a prior court ruling regarding the distribution. This study examines the legal implications and potential problems arising from this practice. Using a normative legal research method with a statutory and conceptual approach, this research finds that the primary problem lies in the potential for future disputes if one party feels aggrieved, as the Notarial deed lacks the res judicata (finality) of a court decision. Furthermore, complications arise regarding the transfer of titles for registered land and buildings at the National Land Agency (BPN), which often requires a specific court order for execution. The results suggest that while a Notarial deed is valid as a consensual agreement under Article 1320 of the Civil Code, it carries a high risk of being challenged or declared "degradable" to a private deed if it fails to fulfill the formal requirements of marital property dissolution. Therefore, Notaries must exercise high levels of caution and provide comprehensive legal counseling to the parties involved.